2009
DOI: 10.1152/ajpendo.00129.2009
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-dependent facilitation on spinal reflex potentiation involves the Cdk5/ERK1/2/NR2B cascade in anesthetized rats

Abstract: TB. Estrogen-dependent facilitation on spinal reflex potentiation involves the Cdk5/ERK1/2/NR2B cascade in anesthetized rats. Am J Physiol Endocrinol Metab 297: E416 -E426, 2009. First published June 16, 2009 doi:10.1152/ajpendo.00129.2009.-Cyclin-dependent kinase-5 (Cdk5), a proline-directed serine/threonine kinase, may alter pain-related neuronal plasticity by regulating extracellular signal-related kinase-1/2 (ERK1/2) activation. This study investigated whether Cdk5-dependent ERK activation underlies the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 93 publications
1
18
0
Order By: Relevance
“…Intrathecal catheter Implantation of intrathecal cannula was performed following the method described in a previous study [13]. Under anesthesia with sodium pentobarbital, the L4-L5 spinal processes were exposed and the muscles beside the processes were isolated bluntly.…”
Section: Methodsmentioning
confidence: 99%
“…Intrathecal catheter Implantation of intrathecal cannula was performed following the method described in a previous study [13]. Under anesthesia with sodium pentobarbital, the L4-L5 spinal processes were exposed and the muscles beside the processes were isolated bluntly.…”
Section: Methodsmentioning
confidence: 99%
“…Mounting evidence indicates that estrogen plays an important role in an extensive spectrum of neural functions, such as nociception (1)(2)(3). The mechanisms by which estrogen modulates pain appear to be highly complex and remain to be elucidated.…”
mentioning
confidence: 99%
“…Estrogen has been reported to rapidly enhance excitatory synaptic transmission, especially via NMDA receptor (NMDAR) 2 -mediated synaptic activity and LTP (8 -13). Estrogen also promotes the formation of new dendritic spines and excitatory synapses in the hippocampus and cortex (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…In the last decade, studies have demonstrated that the interactions between EphBRs and their ephrinB ligands modulate neural plasticity induction in the mammalian central nervous system, mainly, but not exclusively, via exhibiting effects on NMDAR (8,12). A recent study also demonstrated that, in association with thermal hyperalgesia, EphBR activation caused by immunoglobulin fusion protein of ephrinB2 (ephrinB2-Fc)-induced, Src kinase-dependent NR2B phosphorylation in the spinal cord (2), suggesting that ephrinB2-EphBR tyrosine kinase interactions could probably modulate pain signaling via spinal Src-dependent NMDAR phosphorylation (2).Although further proof is still needed for the physiological and/or pathophysiological relevance, the induction of pelvicurethra reflex potentiation (15, 16), a form of NR2B phosphorylation-dependent neural plasticity (5,25,31,41), has been linked to the development of visceral pain from pelvic organs (26,27,30,32,33). Studies have shown that the activation of nociceptive afferent fibers expressing transient receptor potential vanilloid/transient receptor potential ankyrin by the instillation of irritants into the uterus (32, 33) and the descending colon (29) facilitated pelvic-urethra reflex activity in a crossorgan manner.…”
mentioning
confidence: 99%
“…Although further proof is still needed for the physiological and/or pathophysiological relevance, the induction of pelvicurethra reflex potentiation (15, 16), a form of NR2B phosphorylation-dependent neural plasticity (5,25,31,41), has been linked to the development of visceral pain from pelvic organs (26,27,30,32,33). Studies have shown that the activation of nociceptive afferent fibers expressing transient receptor potential vanilloid/transient receptor potential ankyrin by the instillation of irritants into the uterus (32, 33) and the descending colon (29) facilitated pelvic-urethra reflex activity in a crossorgan manner.…”
mentioning
confidence: 99%